Disentangling overlapping seams: The experience of the HILDA Survey - Watson, N (My University, 2014)
An issue unique to longitudinal surveys is seam effects. These occur when there is a tendency for changes in the data to unusually concentrate in adjoining periods from different interviews. One component of the Household, Income and Labour Dynamics in Australia (HILDA) Survey subject to seam effects is the labour market activity calendar. In this calendar respondents are asked to recall the various jobs they have had over a 14 to 18 month period, the time spent in unemployment and the time spent outside the labour force. As the calendar is administered every wave, an overlap of 2 to 6 months results, depending on when the respondent is interviewed. In this paper, we separately model the likelihood that respondents will make three types of errors in the activity calendar. These errors are: i) reporting a spell in the first version of events and not in the second; ii) misplacing a spell in the second version of events compared to the first; and iii) reporting a spell in the second version of events and not in the first. The characteristics considered in the model include the various causes of errors in dating events, such as spell length, spell type, duration of the overlapping seam, recall ability of the respondent, and characteristics of the interview that may affect the respondent’s recall. The overlapping seam also permits the study of measurement error over time to identify whether the same people continually make the same mistakes. With a better understanding of the types of errors that respondents make, the HILDA team hopes to construct a consolidated labour market activity spell file that will encourage greater data use of a section of the HILDA Survey that has so far been underutilised.
Keywords: Surveys and Survey Methodology -- Survey response; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Survey response; Surveys and Survey Methodology